Formation and development of memory studies: the sociological project of M. Halbwachs - Sulzhytski, Ilya S. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the role of the M. Halbwachs sociological project in contemporary memory studies. The first research programs of studying collective memory in sociology are designated. The heuristic potential of the ideas of the French sociological school in the conceptualization of the concept of collective memory is revealed. Features of the M. Halbwachs theory of collective memory and the essence of the concept «social frameworks of memory» are identified. Theoretical distinctions between autobiographical, collective and historical memory are revealed. The main directions of criticism of the works of M. Halbwachs and the possibility of applying his theory in modern memory studies and the sociology of memory are indicated. In conclusion, the importance of sociological theory in the study of collective memory for modern memory studies is substantiated.
Keywords: sociology of memory; M. Halbwachs; memory studies; collective memory